PSIKOEDUKASI KENALI EFIKASI DIRI: ENERGI BAGI MOTIVASI DAN POTENSI PADA SISWA SMA X - Fransisca Iriani Roesmala Dewi; Ruslinda Desiana Ginting (Jurnal Bakti Masyarakat Indonesia, 2023)
SMA X is a favorite school in Pekanbaru City, Riau. The conditions of favorite schools result in dif erences in theexperiences felt by students. There are students who have high self-ef icacy and there are also those who have lowself-ef icacy. Students with low self-ef icacy feel unsure of their ability to complete assignments and achieve desiredgoals. Intervention in the form of psychoeducation with the theme "recognize self-ef icacy: energy for motivationand potential" aims to anticipate this. Students need to be introduced to a concept called self-ef icacy. Thiscommunity service activity aims to increase understanding, knowledge and skills for SMA X students regarding theconcept of self-ef icacy using lecture/knowledge transfer and of line mentoring methods. Self-ef icacy is a student'sbelief in their ability to carry out and complete tasks to achieve the desired goals. The results of the dif erence teston students' pre-test and post-test scores show that there is a significant dif erence between the pre-test and post-testresults, so it can be concluded that psychoeducation has an influence on students' understanding of self-ef icacy.Psychoeducation in community service activities is said to be ef ective because psychoeducation is ef ective inchanging perceptions and increasing students' understanding or cognition regarding self-ef icacy. Students withhigh self-ef icacy are confident in their ability to complete assignments and are able to achieve the expected targets.With high self-ef icacy, it can motivate students to explore their maximum potential and achieve achievements. ABSTRAK SMA X adalah sekolah favorit di Kota Pekanbaru, Riau. Kondisi sekolah favorit mengakibatkan perbedaanpengalaman yang dirasakan oleh para siswa. Ada siswa yang mempunyai efikasi diri yang tinggi dan ada pula yangmemiliki efikasi yang rendah. Siswa dengan efikasi diri rendah merasa tidak yakin akan kemampuannya dalammenyelesaikan tugas dan mencapai tujuan yang diinginkan. Intervensi dalam bentuk psikoedukasi dengan tema“kenali efikasi diri: energi bagi motivasi dan potensi” bertujuan untuk mengantisipasi hal tersebut. Siswa perludiperkenalkan kepada suatu konsep yang disebut efikasi diri. Kegiatan pengabdian kepada masyarakat ini bertujuanuntuk meningkatkan pemahaman, pengetahuan, dan keterampilan kepada para siswa SMA X mengenai konsepefikasi diri dengan metode ceramah/transfer ilmu dan pendampingan secara luring. Efikasi diri merupakankeyakinan siswa terhadap kemampuannya dalam melakukan maupun menyelesaikan tugas untuk meraih tujuan yangdiinginkan. Hasil uji perbedaan terhadap skor pre-test dan post-test para siswa menunjukkan terdapat perbedaanyang signifikan antara hasil pre-test dan post-test sehingga dapat disimpulkan bahwa psikoedukasi berpengaruhterhadap pemahaman siswa mengenai efikasi diri. Psikoedukasi dalam kegiatan pengabdian kepada masyarakat inidikatakan efektif karena psikoedukasi efektif mengubah persepsi dan meningkatkan pemahaman atau kognitif siswamengenai efikasi diri. Siswa dengan efikasi diri yang tinggi yakin akan kemampuannya dalam menyelesaikan tugasdan mampu mencapai target yang diharapkan. Dengan efikasi diri tinggi maka dapat memotivasi siswa untukmenggali potensi yang maksimal dan meraih prestasi.